An acoustics study of the monophthongs of Kedah Malay / Afiqah Jazmin Azli - Afiqah Jazmin, Azli (2017)
The Malay language has a long history and is spoken by many speakers as it has been lingua franca for the speakers in Malaysia, southern Philippines, Indonesia, Singapore as well as Brunei (Asmah, 1982). There are linguistic, extra linguistic and sociolinguistic factors that enabled Malay to become the lingua franca of this region. One of it was due to its simplicity in terms of phonological system (Asmah, 1982). For instance, the vowels in Malay are primary cardinals with the exception for few Malay varieties, such as Kelantan Malay, and the consonants are easier to articulate for nonnative speakers “compared to the Javanese heavy ones” (Asmah, 1982, 4). In addition, the grammatical system of the Malay language also helps to speed up the process of acquiring the language as there are no categories for case, tense, number and gender unlike other languages (Asmah, 1982). Therefore, it is not surprising that the Malay language spread rapidly in this region and become a lingua-franca “as early as the seventh century AD” (Asmah, 1982, 2). This took place when foreign travellers visited the Malay peninsula recorded that the common language used for communication during that time was Malay language. In Malaysia particularly, the spread of the Malay language emerged after gaining independence from Great Britain. The same goes to Indonesia (Asmah, 1982). Upon independence, the use of the language in official functions, educational institutions and government administration increased.